THE CONTENT OF QUALIFICATION OF CRIMES - V. Veklenko; V. Neshataev (Правоприменение, 2017)
УДК 343(2+7)The main provisions of the theory of qualification of crimes were developed in the Soviet times. Some of them, notably relating to the content of criminal law assessment, have become obsolete. Therefore, the article aims to interpret a new vision of the content of qualification. The methods used in the research include analysis, synthesis, induction, deduction, interview and statistical method. The authors note that in practice, in fact, general and specific signs of the crimes appearing in the criminal law are used in the qualification of crime.The authors question the use of "corpus delicti" in enforcement during the criminal legal evaluation. Corpus delicti was created in science to the full understanding and disclosure of the crime and its possible structures. It is impossible to carry out qualification and to resolve issues of criminal responsibility or exemption from it on the basis of scientific statements, which are not enshrined in law.Without knowledge of corpus delicti it is possible to hold a formal qualification of the offences and the imposition of criminal liability. This is due to the fact that all penal signs, sufficient for criminal liability provided for in the existing criminal law of the Russian Federation.The authors make the conclusion that qualification is carried out not in terms of corpus delicti, which is a scientific category, but on the basis of general features of crime – guilt, social danger, unlawfulness, liability to punishment, since it is them that are consolidated on the legislative level.